Up-conversion luminescence of Er3+ and Yb3+ co-doped CaBi2Ta2O9 multifunctional ferroelectrics - Qiufeng Cao (Journal of Advanced Dielectrics, 2014)
Er3+ and Yb3+ co-doped CaBi2Ta2O9 (CBT)-based bismuth layered-structure oxides were synthesized by a simple solid-state reaction method. Their up-conversion (UC) luminescence, dielectric and ferroelectric properties were investigated. Two strong green emission bands centered at 526 and 547 nm and a weak red emission band centered at 658 nm were obtained under a 980 nm laser excitation at room temperature. These emission bands originated from the radiative relaxation of Er3+ from 2H11/2, 4S3/2, and 4F9/2 levels to the ground state 4I15/2, respectively. At the meantime, the fluorescence intensity ratio (FIR) variation of two green UC emissions at 526 and 547 nm has been studied as a function of temperature in the range of 153–603 K. The maximum sensor sensitivity obtained was 39 × 10-4 K-1 at 590 K, which indicated that Er3+/Yb3+ co-doped CBT ceramic is a promising candidate for applications in optical high temperature sensor.